Pemolisian Intervensi dalam Situasi Kedaruratan: Studi Kasus Strategi Polresta Bogor dalam Penanggulangan Pandemi Covid-19 di Kota Bogor, Jawa Barat : Intervention Policing; Covid-19 pandemic; Emergency Situation - Condro, Susatyo Purnomo; Purwanto, Semiarto Aji; Setyabudi, Chairul Muriman (Jurnal Keamanan Nasional, 2022)
This article argues for the importance of building an intervention-based policing model in an emergency situation. Through a case study of the Bogor Police’s strategy in dealing with the COVID-19 pandemic, this article finds gaps in empirical and theoretical developments regarding the effectiveness of modern democracy-based and community-based policing models in the midst of the Covid-19 pandemic. This article looks at the importance of the intervention policing paradigm, which is a combination of values-based regulation in the community and the legitimacy-based regulation of the police authority. The intervention policing model emphasizes the importance of three police intervention approaches; participatory intervention, institutional intervention, and regulatory intervention as a policing model in emergency situations such as the COVID-19 pandemic.